Molecular Characteristics of m6A Regulators and Tumor Microenvironment Infiltration in Soft Tissue Sarcoma: A Gene-Based Study - Xiao, Kang-Wen; Yang, Zhi-Qiang; Yan, Xin; Liu, Zhi-Bo; Yang, Min; Guo, Liang-Yu; Cai, Lin (Frontiers in Bioengineering and Biotechnology, 2022)
Background: N6-methyladenosine (m6A) methylation played a key role in tumor growth. However, the relationship between m6A and soft tissue sarcoma (STS) was still unclear. Methods: The characterization and patterns of m6A modification in STS (TCGA-SARC and GSE17674) was analyzed comprehensively through bioinformatics and real-time polymerase chain reaction (RT-PCR). Effects of different m6A modification patterns on prognosis and immune infiltration of STS were further explored. Differential expressed genes (DEGs) analysis was performed. Moreover, an m6Ascore was constructed by principal component analysis (PCA). Besides, two immunotherapy datasets (IMvigor210 and GSE78220) and a sarcoma dataset (GSE17618) were used to evaluate the m6Ascore. Results: Huge differences were found in somatic mutation, CNV and expression of 25 m6A regulators in STS. 2 modification patterns (A and B) in STS were further identified and the m6A cluster A showed a better clinical outcome with lower immune/ stromal score compared with the m6A cluster B (p < 0.050). Besides, most of STS samples from m6A cluster A showed high m6Ascore, which was related to mismatch repair and better prognosis of STS (p < 0.001). In contrast, the m6A cluster B, characterized by low m6Ascore, was related to MYC signaling pathway, which led to poor prognosis of STS. High m6Ascore also contributed to better outcome of PD-1/PD-L1 blockade immunotherapy. Conclusions: The modification patterns of 25 m6A regulators in STS microenvironment were explored comprehensively. The novel m6Ascore effectively predicted the characteristics of tumor microenvironment (TME) and outcome in STS, and provided novel insights for future immunotherapy.